1983
DOI: 10.1111/j.1600-065x.1983.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA and Susceptibility to Leprosy

Abstract: This review examines the evidence for involvement of MHC-associated factors in host immune response to Mycobacterium leprae, by collating HLA studies of sporadic and familial leprosy and discussing possible HLA-related immunological mechanisms in determining host response. Formal linkage analysis of 109 multiple-case families with data available for HLA haplotype segregation showed that under a three-allele recessive model for susceptibility to leprosy, linkage was observed between the HLA complex and a lepros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 50 publications
(29 reference statements)
3
25
0
Order By: Relevance
“…[14][15][16][17][18][19][20] Recently an HLA-B46, MICA-5A5 haplotype was found less often amongst multibacillary leprosy patients compared to controls in a small south China study, indicating that this haplotype may carry a gene that is protective against multibacillary leprosy in this population. 21 MICA itself is a candidate susceptibility locus: located in the HLA class I region, MHC class 1 chainrelated (MIC) genes encode membrane-bound polypeptides that do not bind peptides or associate with b2-microglobulin, but instead act as a co-stimulatory signal by interaction with a receptor NKG2D to augment T-cell activation.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Recently an HLA-B46, MICA-5A5 haplotype was found less often amongst multibacillary leprosy patients compared to controls in a small south China study, indicating that this haplotype may carry a gene that is protective against multibacillary leprosy in this population. 21 MICA itself is a candidate susceptibility locus: located in the HLA class I region, MHC class 1 chainrelated (MIC) genes encode membrane-bound polypeptides that do not bind peptides or associate with b2-microglobulin, but instead act as a co-stimulatory signal by interaction with a receptor NKG2D to augment T-cell activation.…”
mentioning
confidence: 99%
“…47 recessive inheritance of HLA-linked susceptibility to tuberculoid leprosy. 48 In one of the above-mentioned family studies in India46 HLA-DR2 was observed to be associated with tuberculoid leprosy. Although this finding was confirmed in a subsequent family study,49 the frequency of DR2 among sporadic cases of tuberculoid leprosy in the same Indian area was shown not to be increased,50 suggesting a genetic heterogeneity between familial and sporadic tuberculoid leprosy.…”
Section: Studies Of Hla and Tuberculoid Leprosymentioning
confidence: 98%
“…57. 48 The family data fr om Venezuela, however, attempted to break with this ill-based dogma. The segregation pattern was fo und to be highly non-random, especially for haplo types derived fr om lepromatous (BL and LL) leprosy-affected parents.…”
Section: Studies Of Hla and Tuberculoid Leprosymentioning
confidence: 99%
“…136 Several studies comparing HLA Class I gene frequencies in leprosy cases and controls have found associations either with the polar forms of leprosy, or with leprosy itself, however these suggested associations have not been replicated as they are limited and inconsistent. 130,[137][138][139][140][141][142] The association between DR and DQ alleles and different clinical subtypes of leprosy are documented. Several studies reported an association of the HLA-DR2 alleles; HLA -DRB1*15, *16, *10 and *12 with susceptibility or resistance to leprosy in Brazilian, Vietnamese, South Indian, Indonesian, Thai and Argentine populations.…”
Section: -133mentioning
confidence: 99%